Transactions on Engineering Technologies World Congress on Engineering and Computer Science 2017 - Ao, Sio-Iong; Kim, Haeng Kon; Amouzegar, Mahyar A. (Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains a selection of revised and extended research articles written by prominent researchers participating in a large international conference on Advances in Engineering Technologies and Physical Science which was held in San Francisco, California, USA, October 25-27, 2017. Topics covered include engineering mathematics, electrical engineering, communications systems, computer science, chemical engineering, systems engineering, manufacturing engineering, and industrial applications. With contributions carefully chosen to represent the most cutting-edge research presented during the conference, the book contains some of the state-of-the-art in engineering technologies and the physical sciences and their applications, and serves as a useful reference for researchers and graduate students working in these fields.